Sanksi Pidana Terhadap Pelaku Usaha dalam Memperjual Belikan Produk Makanan yang Telah Melewati Waktu Pemakaian - Darly Taruna; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
The expiry period of the product is very important for consumers who enjoy the product for consumption, because it concerns the health of the body so that the community as well as social creatures who need clothing and food must be more careful in choosing products that can really protect themselves so as not to lose themselves. (1) What is the legal protection of consumers for expired food circulating in the community?, (2) What is the accountability of business actors for the circulation of expired food under the Consumer Protection Law? The method used is the normative legal research method. The implementation of consumer protection of expired packaged foods that are basically carried out by business actors, governments, nongovernmental organizations and consumers is with various efforts. Accountability for products that have been traded by business actors and that have been circulated to the market or consumers becomes the responsibility that circulates the product, namely business actors.